Investigation of Acoustic and Electrical Properties of a LIPO3 Metaphosphate Glass - Peter Hockicko; Peter Bury; Francisco Munoz; Laura Munoz-Senovilla (Communications - Scientific letters of the University of Zilina, 2014)
The acoustic attenuation spectroscopy in connection with conductivity and dielectric relaxation spectroscopy can be useful techniques for the study of relaxation processes and transport mechanisms in Li+ ion conducting glasses. A theoretical model and mathematical fit of acoustic and conductivity measurements are used for characterization of the ionic hopping motion, relaxation processes and transport mechanisms connected with the mobility of conducting Li+ ions. Results from acoustic measurements are compared with results obtained from electrical conductivity measurements.